2018
DOI: 10.1111/dme.13619
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of medication adherence and glycaemic control and their implications for direct outpatient medical costs: a cross‐sectional study

Abstract: Identifying the influence of the sequential mediating effects of distress and perception was important in understanding the pathway between medication adherence and glycaemic control. This suggests the importance of a team-based approach to address these mediators and thus improve glycaemic control. Poor glycaemic control was also found to be associated with higher direct medical costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Adherence to medical instructions and glycemic control are affected by several factors such as knowledge about diabetes [13], self-efficacy [14–17], depression [1820], medical beliefs [21, 22], medical cost, and social support. Disease perception is thought to be an important psychosocial factor that can motivate patients to self-manage their diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to medical instructions and glycemic control are affected by several factors such as knowledge about diabetes [13], self-efficacy [14–17], depression [1820], medical beliefs [21, 22], medical cost, and social support. Disease perception is thought to be an important psychosocial factor that can motivate patients to self-manage their diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Some recent examples of articles referring to mediation analyses with PROCESS (Hayes, 2013) Reference Indirect effect(s) of… Issues Alt et al (in press) …stereotype valence on favorable evaluations through perceived offensiveness -Followed the causal steps logic by highlighting that "the direct effect […] was no longer significant" (pp. 6, 7, 10) Bender et al (2018) …closeness, dependability, and anxiety on resilience through self-care and selfefficacy -Followed the causal steps logic by stating that significant direct effects suggest "partial mediation" (p. 19) Bhalla et al (2018) …exposure to potentially morally injurious events on sexual anxiety through emotional numbing -Followed the causal steps logic by stating that "this was a partial mediation, as the direct effect […] remained significant" (p. 424) Buckner et al (2018) …cannabis use on condom use through protective behavior strategies -Followed the causal steps logic by highlighting that "there was no longer a significant direct effect" (p. 52) Feinberg et al (2018) …experiential avoidance on accommodation through beliefs about anxiety -Followed the causal steps logic by highlighting that "when negative beliefs about child anxiety were incorporated into the model this direct effect was no longer significant" (p. 652) Friese et al (in press) …ego depletion on performance through monitoring processes and selfefficacy -Followed the causal steps logic by describing mediation in terms of the Baron and Kenny approach (p. 9) -Confused total effect with direct effect Karriker-Jaffe et al 2018…treatment type on alcohol consumption through treatment duration and Alcoholics Anonymous attendance -Followed the causal steps logic by stating that "effects of treatment type on alcohol consumption [are] partially mediated by Alcoholics Anonymous attendance" (p. 596) Li et al (2018) …injunctive and descriptive norms on willingness to quit smoking through smoking risk perception -Used 1,000 bootstrap samples although Hayes (2013) recommends using a minimum of 5,000 bootstrap samples -Followed the causal steps logic by stating that "smoking risk perception partially mediated the association between descriptive norms and willingness to quit smoking" (p. 277) Lum et al (2018) …medication adherence on glycated hemoglobin concentration through diabetes-related distress and perception of hyperglycaemia -Tested simple mediation models with the causal steps approach and the Sobel test, but a subsequent multiple mediation model with PROCESS/bootstrapping (p. 810) -Followed the causal steps logic by referring to full/complete vs. partial mediation Mackenbach et al (in press) …access to fast food outlets on overweight through perceived availability and usage of fast food outlets -Tested mediation effects with the Sobel test -Followed the causal steps logic by not testing for mediation for certain outcomes because "n...…”
Section: Open Science Practicesmentioning
confidence: 99%
“…For glucose‐lowering treatment, there is some evidence that adherence to metformin is less than that to sulfonylureas and thiazolidinediones, which, in turn, show lower adherence than that to dipeptidyl peptidase 4 inhibitors (DPP‐4i) . Indeed, an important caveat from a large pharmacy database study of people given second‐line treatment after metformin showed that fewer than 10% had definite evidence of having taken metformin in the recommended dosage, and that 28% had no prior claim evidence of having received the medicine at all! Certainly, one would expect that greater levels of adherence would lead to greater degrees of improvement in glycemia, and there is evidence that this is true for oral hypoglycemic agents, with a report from the UK Clinical Practice Database Study showing nearly twice as great an improvement in HbA1c in adherent people receiving oral hypoglycemic treatment, but the mechanism of this association may not simply reflect the pharmacologic action of the medication, with evidence that psychological factors associated with greater medication adherence may track with glycemic improvement . Issues of adherence are particularly great with injected diabetes treatments.…”
mentioning
confidence: 99%